Revisiting Lung Cancer Metastasis: Insight From the Functions of Long Non-coding RNAs. (August 2021) - Huang, Peng; Zhu, Shaomi; Liang, Xin; Zhang, Qinxiu; Liu, Chi; Song, Linjiang
Globally, lung cancer is the most common cause of cancer-related deaths. After diagnosis at all stages, <7% of patients survive for 10 years. Thus, diagnosis at later stages and the lack of effective and personalized drugs reflect a significant need to better understand the mechanisms underpinning lung cancer progression. Metastasis should be responsible for the high lethality and recurrence rates seen in lung cancer. Metastasis depends on multiple crucial steps, including epithelial–mesenchymal transition, vascular remodeling, and colonization. Therefore, in-depth investigations of metastatic molecular mechanisms can provide valuable insights for lung cancer treatment. Recently, long noncoding RNAs (lncRNAs) have attracted considerable attention owing to their complex roles in cancer progression. In lung cancer, multiple lncRNAs have been reported to regulate metastasis. In this review, we highlight the major molecular mechanisms underlying lncRNA-mediated regulation of lung cancer metastasis, including (1) lncRNAs acting as competing endogenous RNAs, (2) lncRNAs regulating the transduction of several signal pathways, and (3) lncRNA coordination with enhancer of zeste homolog 2. Thus, lncRNAs appear to execute their functions on lung cancer metastasis by regulating angiogenesis, autophagy, aerobic glycolysis, and immune escape. However, more comprehensive studies are required to characterize these lncRNA regulatory networks in lung cancer metastasis, which can provide promising and innovative novel therapeutic strategies to combat this disease.